Effect of Running Exercise on Oxidative Stress Biomarkers: A Systematic Review - Thirupathi, Anand; Pinho, Ricardo A.; Ugbolue, Ukadike C.; He, Yuhuan; Meng, Yao; Gu, Yaodong (Frontiers in Physiology, 2021)
Background: Exercise induced health benefits are limited by the over accumulation of reactive oxygen species (ROS). ROS and further oxidative stress could potentially induce muscle damage which could result in poor exercise performance. However, predicting ROS induced oxidative stress in response to endurance training has several limitations in terms of selecting biomarkers that are used to measure oxidative stress. Objective: The purpose of this study was to systematically investigate the suitable biomarkers that predicts oxidative stress status among the runners. Methods: According to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement, a search for relevant articles was carried out on PubMed/Medline, ISI Web of Science and Google Scholar using related terms such as oxidative damage, ROS, exercise, physical training, running, marathon and ultramarathon. Results: Outcomes included (1) running programs like half-marathon, ultramarathon and iron-man race, (2) measuring biochemical assessment of oxidative damage markers such as malondialdehyde (MDA), protein carbonyl (PC), total antioxidant capacity (TAC), thiobarbituric acid reactive substances (TBARS), 8-Oxo-2'-deoxyguanosine (8-OH-dG), 4-hydroxynonenal (HNE), and F1-isoprostones, and enzymatic and nonenzymatic antioxidants level. Conclusions: This study concluded that running exercise does not elicited response to specific biomarkers of oxidative stress, instead, oxidative damage markers of lipids, proteins, and various enzymatic and nonenzymatic antioxidants expressed according to the training status of the individual.